Pengaruh Metode Mendongeng terhadap Kecerdasan Emosi Anak - Laiya, Sri Wahyuningsi; Sutisna, Icam; Daud, Nirmala; MM Shodiq, Nurul Aini (Jambura Early Childhood Education Journal, 2023)
Abstract Emotional intelligence at TK Mekar Hulawa remains low where it is due to less attractive method applied to introduce them about emotion. Consequently, the children are less enthusiastic about participating in the learning process. The current research aims to determine whether or not there is an effect of storytelling method on emotional intelligence in children aged 5 -6 years at TK Mekar Hulawa. This research is classified as quantitative experimental research with Pre-Experimental One Group Pre-Test Posttest Design. The population in this research is 30 children, whereas the samples are 19 children in class B. The research finding shows that the Pre-Test data indicate an average value of 17,52 and standard deviation of 2,912. Meanwhile, the Posttest data indicate an average value of 26,684 and standard deviation of 3,682. The findings denote that the average respondents’ result increases from the initial test to the final test. In addition, the result of tcount is 2,947 with ttable of 2,101. Therefore, the tcount is greater than the ttable, so it can be concluded that H0 is rejected and H1 is accepted. In other words, there is an effect of storytelling method on emotional intelligence in children aged 5-6 years at TK Mekar Hulawa, Telaga Subdistrict, Gorontalo Regency.